A corpus-based study of the translation of modal verbs in the three versions of Shih chi - Yang, Lei; Zhang, Yue; Duan, Manfu (Frontiers in Psychology, 2023)
Modality plays an important part in verbal communication, as it can reveal the speaker’s views and perspectives. The modal verb, as an essential component of the modality system, has been a hot research topic and a challenge in academic circles in recent years. Analyzing the modal verbs in a text may indicate the context produced by the translator in the translation and the identity difference between the translator and the reader. In this study, three representative English translations of Shih chi are selected for comparative analysis with the original text. With the help of corpus techniques, the paper investigates the differences in the use of modal verbs by various translators, the distribution of quantitative changes and their influence on translations, as well as the historical and cultural backgrounds and identities of the translators that led to these differences. It is found that owing to the different professional identities of the translators and historical and cultural contexts in which they live, the choice of modal verbs and the shifts of modality values in the three translations are distinct, leading to different translation styles.